COMMUNITY PARTICIPATION IN REDUCING THE RISK OF WASTE POLLUTION IN TANJUNG BARU VILLAGE, TANJUNG MORAWA DISTRICT - Riyan Asmara Jisa; Muniruddin (SOSIOEDUKASI, 2025)
This study aims to determine the form of community participation in reducing the risk of waste pollution in Tanjung Baru Village, Morawa District. The problem of village waste is a critical issue because it can have negative impacts on health, the environment, and the quality of life of the community if not handled properly. This study used a qualitative descriptive approach with observation, interviews, and documentation methods to explore community participation in maintaining environmental cleanliness. The results show that community participation is manifested in various forms, including household waste management, mutual cooperation activities to clean the environment, the utilization of organic waste into compost, and awareness of disposing of waste in the provided bins. Obstacles faced by the community include limited waste management facilities, lack of knowledge about the impacts of waste, and low awareness of some residents. Nevertheless, in general, the community shows a fairly good concern in efforts to reduce the risk of village waste pollution. Thus, the active role of the community is very important and needs to be increased through counseling, mentoring, and the provision of adequate waste management facilities to create a clean, healthy, and sustainable village environment.